2016
DOI: 10.1111/risa.12548
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Local Policy Elites’ Perceptions on the Benefits and Risks Associated with High‐Voltage Power Line Installations in the State of Arkansas

Abstract: Recently, a controversial policy debate has arisen concerning the installation of high-voltage power lines in northwest Arkansas. While proponents argue that such an installation is inevitable to efficiently and reliably support the identified electric load in the region, opponents claim that the lines will degrade the natural environment and hamper the tourism-based local economy in affected regions, notably in Ozark Mountain areas. Of particular interest is to understand how local policy elites perceive the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Additionally, this study provides valuable information for CT researchers with regard to treatment of fatalists. Often, fatalists are completely ignored in studies utilizing CT, as, at least by theory, they are not expected to have any significant relationships with variables of interest . However, this study sheds some light on what may be occurring with fatalists.…”
Section: Conclusion and Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Additionally, this study provides valuable information for CT researchers with regard to treatment of fatalists. Often, fatalists are completely ignored in studies utilizing CT, as, at least by theory, they are not expected to have any significant relationships with variables of interest . However, this study sheds some light on what may be occurring with fatalists.…”
Section: Conclusion and Discussionmentioning
confidence: 89%
“…Many previous studies have shown that cultural value predispositions influence perceptions of risk across an array of substantive domains . However, the causal mechanism through which this relationship occurs has been underspecified, at best.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to address the problem of narrative relativity (Jones, ), we leverage Cultural Theory (CT) to populate our narratives with generalizable symbols, wording, and content. CT is an approach originally developed by Mary Douglas () and then further formalized to include grid/group dimensions of sociality, where group denotes the extent to which individuals prefer and associate in groups while grid denotes the extent to which those groups prescribe and constrain preferences and behavior (e.g., Moyer & Song, ; Ripberger, Song, Nowlin, Jones, & Jenkins‐Smith, ; Song, ; Song, Silva, & Jenkins‐Smith, ; Thompson, Ellis, & Wildavsky, ; Tumlison, Moyer, & Song, ). By intersecting the dimensions of grid and group, CT can be used to conceptually classify individuals as one of four cultural types: egalitarian (low grid/high group), hierarch (high grid/high group), individualist (low grid/low group), and fatalist (high grid/low group).…”
Section: Narrative Policy Framework Cultural Theory and Culturally mentioning
confidence: 99%